The Urgency of Adversity Quotient for Women Running the Small Businesses - Mar'atus Sholikhah; Faraz Faraz (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2021)
During the economic crisis occurring in Indonesian, entrepreneurial sector has been the solution for Indonesian economic downturn. Until the current time, entrepreneurship keeps becoming the cornerstone for the government in improving Indonesia economic growth. However, entrepreneur women face more specific obstacles which complicate their steps, then it causes the fact that there are more entrepreneur women have contributions in Indonesian economic growth (60%) is less exposed (Tjahjadi et al., 2019). The study is aimed to identify the relationship between adversity quotients with entrepreneurial intentions of entrepreneur women. The hypothesis proposed in this study is that there is a positive relationship between adversity quotients with entrepreneurial intentions of entrepreneur women. The research subjects were 100 batik entrepreneur women. The scale used in this study was made based on the aspects of the Theory Planned Behavior (TPB) by Ajzen for the entrepreneurial intention variable and aspects of the Adversity Response Profile (ARP) by Stotlz for the adversity quotient variable. The hypothesis test result using Pearson's product-moment showed a correlation number r of .497 and p = .000 (p < .01). It indicates that there is a significant relationship between Adversity Quotient and Entrepreneurial Intensity so that the proposed hypothesis is accepted. The implication of the research is for encouraging the entrepreneur women to create solution to overcome adversities in developing the business.